GRUPO REFLEXIVO COM HOMENS AGRESSORES - Santos, Bruna Oliveira; Hasse, Barbara Gusso; Brandao, Josiane Da Silva; Dos Santos, Elisangela Maria Almeida; Piber, Lizete Dieguez; Perlin, Ana Priscila Dos Santos (Salão do Conhecimento, 2018)
Projeto de Iniciação Cientifica